Mechanism of Corpus Callosum Infarction Associated with Acute Hydrocephalus: Clinical, Surgical, and Radiological Evaluations for Pathophysiology - Hirono, Seiichiro; Kawauchi, Daisuke; Kobayashi, Masayoshi; Orimoto, Ryosuke; Ikegami, Shiro; Horiguchi, Kentaro; Iwadate, Yasuo (World neurosurgery, 2019)
Corpus callosum (CC) infarction has been reported to be rare because of the rich blood supply in the CC. The pathophysiology of CC infarction associated with acute hydrocephalus is unknown. The aim of the present study was to clarify the characteristics and mechanism of CC infarction associated with acute noncommunicating hydrocephalus (ANCH). We reviewed clinical the data from all patients who had undergone surgical intervention for ANCH at Chiba University Hospital from January 2008 to March 2018. Patients with vascular lesions, a history of hydrocephalus, and lacking magnetic resonance imaging studies were excluded. The clinical, surgical, and radiological parameters were obtained retrospectively for pathophysiological analysis. A total of 23 patients with ANCH who had undergone surgical intervention and had met the inclusion criteria were included in the present study. Of the 23 patients, 6 (23%) had developed CC infarction. All CC infarctions were located in the splenium. Although no clinical or surgical features were associated with splenial infarction, the radiological parameters of lateral ventricle enlargement and a narrower callosal angle at the posterior commissure and the foramen of Monro were significantly associated with splenial infarction. The present study has presented evidence that increased intraventricular pressure by ANCH applied transversely in the splenium will directly induce compression of the superior branch of the posterior callosal artery and pericallosal pial plexus, resulting in splenium-specific infarction in patients with ANCH.